Understanding conflicts between nomadic clans in Somalia’s Mudug region - Abdullahi, Said; Takaindisa, Joyce (2025)
Climate change and variability have intensified the frequency and severity of droughts in Somalia, depleting vital natural resources such as water and pasture that sustain pastoral livelihoods in recent years. As a result, herders have suffered massive livestock deaths, which in turn have eroded household incomes, deepened food insecurity, and forced families into displacement in search of relief. Somalia has also experienced recurring and deadly inter-clan conflicts, primarily among nomadic clans competing over scarce water and pasture resources. These conflicts have driven large-scale displacement, with an estimated 250,000 people forced to flee their homes in 2024 alone. This report examines the key drivers of these conflicts and proposes actionable, context-specific solutions to strengthen peacebuilding efforts in Mudug and across Somalia